A biochar-based ion-imprinted polymer material and its preparation method and application

By using biochar-based ion-blotting polymer materials in soil pollution repair, the problem of poor compatibility between existing materials and soil is solved, and the effect of efficient adsorbing arsenic pollutants in soil is achieved, and the material cost is reduced.

CN116693757BActive Publication Date: 2025-03-14BEIJING UNIV OF CHEM TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310560622.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-05-18
Publication Date
2025-03-14
Estimated Expiration
2043-05-18

AI Technical Summary

Technical Problem

Existing ion-blotting polymers are limited in the application of soil pollution repair due to poor soil compatibility.

Method used

Biochar is used as the matrix and 4-vinylpyridine as the functional monomer to prepare biochar-based ion-blotting polymer materials through two steps: Reaction I and Reaction II.

Benefits of technology

The material has good soil compatibility and high adsorption selectivity, and has good selective adsorption effect on free arsenic in the soil, and is cheap.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116693757B_ABST
    Figure CN116693757B_ABST
Patent Text Reader

Abstract

A biochar-based ion-imprinted polymer material and its preparation method and application belong to the field of material preparation. The preparation method comprises: reacting a mixed solution containing a template and 4-vinylpyridine I to obtain a reaction system I, wherein the template is a metalloid compound or a heavy metal compound; adding biochar, a cross-linking agent, and an initiator to the reaction system I to carry out reaction II, washing, and drying to obtain a biochar-based ion-imprinted polymer material. When the material is used as a fixation / stabilization material for arsenic-containing soil remediation, it can be evenly distributed in the soil without causing agglomeration problems, can stably exist in a complex soil environment, has a good selective adsorption effect on free arsenic in the soil, and has a good short-term fixation effect. In addition, the material is a neutral material and has almost no effect on soil pH.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of material preparation, and in particular to a biochar-based ion-imprinted polymer material and a preparation method and application thereof. Background Art

[0002] In the field of soil pollution remediation, arsenic contamination in the soil has become an urgent problem to be solved because of the wide distribution of polluted sites, the profound and lasting impact on the agriculture and animal husbandry industries, and the great harm to the human body.

[0003] Because ion-imprinted polymers have holes corresponding to target ions, they can accurately bind to target ions in the environment and show good results in the treatment of arsenic pollutants in water bodies.

[0004] Existing ion-imprinted polymers are difficult to apply in soil pollution remediation due to problems such as poor compatibility with soil. Summary of the invention

[0005] (I) Purpose of the invention

[0006] The purpose of the present invention is to provide a biochar-based ion-imprinted polymer material and a preparation method and application thereof, wherein the material has the advantages of low cost and good compatibility with soil.

[0007] (II) Technical solution

[0008] To solve the above problems, the first aspect of the present invention provides a method for preparing a biochar-based ion-imprinted polymer material, comprising:

[0009] Conducting a reaction I on a mixed solution containing a template and 4-vinylpyridine to obtain a reaction system I, wherein the template is a metalloid compound or a heavy metal compound;

[0010] Add biochar, a cross-linking agent and an initiator into the reaction system I to carry out reaction II, wash and dry to obtain a biochar-based ion-imprinted polymer material.

[0011] Specifically, the specific conditions of reaction I include:

[0012] Carry out under stirring conditions;

[0013] The reaction temperature is 10-40°C;

[0014] The reaction time is 10 to 50 minutes.

[0015] Preferably, the reaction time is 25 to 35 minutes.

[0016] Specifically, the template agent is sodium arsenite;

[0017] Specifically, the cross-linking agent is ethylene glycol dimethacrylate;

[0018] Specifically, the initiator is azobisisobutyronitrile.

[0019] Specifically, the mass ratio of the template, 4-vinylpyridine, biochar, cross-linking agent, and initiator is 1: 2.72-4.08: 6.10-18.30: 24.21-36.21: 0.61-0.92.

[0020] Furthermore, the mixed solution further comprises a solvent, and the solvent is selected from at least one of methanol, ethanol, acetic acid, and acetic acid;

[0021] The amount of the solvent used is 100 to 300 times that of 4-vinylpyridine.

[0022] Specifically, the specific conditions of reaction II include:

[0023] Carry out under stirring and inert atmosphere;

[0024] React at 15-30°C for 50-60 min, raise the temperature to 50-65°C, and react for 10-12 h.

[0025] In another aspect, the present invention provides a biochar-based ion-imprinted polymer material prepared by any of the methods described above.

[0026] In another aspect of the present invention, there is provided the use of the biochar-based ion-imprinted polymer material prepared by any of the above methods in the field of environmental remediation.

[0027] Specifically, its application in the solidification of arsenic contaminants in soil.

[0028] (III) Beneficial effects

[0029] The present invention provides a method for preparing a biochar-based ion-imprinted polymer material. By using biochar as a material matrix and 4-vinylpyridine as a functional monomer of the ion-imprinted polymer, the prepared polymer is evenly distributed on the surface of the biochar. Not only can the active holes of the ion-imprinted polymer better adapt to the structure of arsenite ions, so that the arsenite ions can be specifically identified in a multi-ion system, showing high adsorption selectivity and improving the use efficiency of the material, but also the polymer material can have a strong affinity for the soil, thereby avoiding major changes to the soil environment and protecting the original environment.

[0030] The biochar-based ion-imprinted polymer material provided by the present invention is applied to a water environment with multiple ions and exhibits good adsorption selectivity for free arsenic pollutants, with an adsorption capacity of up to 70 mg / g.

[0031] When this material is used as a fixation / stabilization material for the remediation of arsenic-containing soil, it can be evenly distributed in the soil without causing caking problems. It can exist stably in complex soil environments, has a good selective adsorption effect on free arsenic in the soil, and has a good short-term fixation effect. In addition, this material is a neutral material and has almost no effect on soil pH.

[0032] The material introduces a large amount of low-cost biochar, reducing the material cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 are scanning electron microscope (SEM) images of biochar and biochar-based arsenic ion imprinted polymer materials, wherein a is a scanning electron microscope image of biochar, and b is a scanning electron microscope (SEM) image of the biochar-based arsenic ion imprinted polymer material provided in Example 1;

[0034] Figure 2 Energy dispersive spectrometry (EDS) images of the scanning electron microscope (SEM) images of the biochar-based arsenic ion imprinted polymer material provided in Example 1, wherein a is an SEM image of the biochar without the imprinted polymer loaded, and b is an SEM image of the imprinted polymer wrapped on the surface of the biochar;

[0035] Figure 3 Thermogravimetric curve of the biochar-based arsenic ion imprinted polymer provided in Example 1;

[0036] Figure 4 The adsorption thermodynamic curve of the biochar-based arsenic ion imprinted polymer provided in Example 1;

[0037] Figure 5 This is a multi-ion system adsorption selectivity effect diagram of the biochar-based arsenic ion imprinted polymer provided in Example 1;

[0038] Figure 6 A diagram showing the preliminary fixation effect of the biochar-based arsenic ion imprinted polymer under laboratory conditions provided in Example 1;

[0039] Figure 7 This is a diagram showing the in-situ fixation effect of the biochar-based arsenic ion imprinted polymer provided in Example 1 on mining area soil. DETAILED DESCRIPTION

[0040] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with specific embodiments and with reference to the accompanying drawings. It should be understood that these descriptions are only exemplary and are not intended to limit the scope of the present invention. In addition, in the following description, the description of well-known structures and technologies is omitted to avoid unnecessary confusion of the concept of the present invention.

[0041] An embodiment of the present invention provides a method for preparing biochar, comprising the following steps:

[0042] Drying the kitchen waste at 100-105°C to obtain dry raw materials;

[0043] The obtained dry raw material is prepared into biochar by a hydrothermal method in a high-pressure reactor. The specific preparation method includes:

[0044] The heating rate was 3-5°C / min, the temperature was raised to 280-300°C, maintained for 2-3h, and then cooled to room temperature. The wet biochar was obtained by vacuum filtration, first rinsed with anhydrous ethanol and then with pure water, and then dried at 100-105°C, ground with a mortar, and then screened with a 100-mesh sieve to prepare the final biochar.

[0045] This method uses kitchen waste as raw material, has low production cost and wide source of raw materials.

[0046] Another embodiment of the present invention provides a method for preparing a biochar-based ion-imprinted polymer material, comprising:

[0047] Step 1: performing reaction I on a mixed solution containing a template agent and 4-vinylpyridine to obtain a reaction system I, wherein the template agent is arsenite;

[0048] Step 2: Add the biochar, crosslinking agent and initiator prepared in the above embodiment to the reaction system I to carry out reaction II, wash and dry to obtain the biochar-based ion-imprinted polymer material.

[0049] The specific conditions of reaction I in step 1 include:

[0050] The stirring is carried out, preferably, the rotation speed is 600-800 rpm;

[0051] The room temperature in the embodiment of the present invention refers to a room temperature environment of 10 to 35°C;

[0052] The reaction temperature is 10-40°C;

[0053] The reaction time is 10 to 50 minutes.

[0054] Preferably, the reaction time is 25 to 35 minutes. When the reaction time is controlled at 25 to 35 minutes, the adsorption amount of arsenic ions by the biochar-based ion-imprinted polymer material in the water body with the target pollutants can reach 70 mg / g or more. In the present invention, the adsorption amount refers to the mass of the target pollutant adsorbed and fixed per gram of material, and the fixation efficiency refers to the ratio of the fixed amount of the free target pollutant to the total amount of the original free target pollutant, expressed as a percentage by mass.

[0055] Preferably, the crosslinking agent is ethylene glycol dimethacrylate; and the initiator is azobisisobutyronitrile.

[0056] Preferably, the mass ratio of the template, 4-vinylpyridine, biochar, cross-linking agent, and initiator is 1: 2.72-4.08: 6.10-18.30: 24.21-36.21: 0.61-0.92. When the reactant ratio is within this range, the material can fix the target pollutant in an aquatic environment where only the target pollutant exists. The efficiency can reach 50 mg / g or more. More preferably, the mass ratio of the template, 4-vinylpyridine, biochar, cross-linking agent, and initiator is 1: 2.72-4.08: 6.10-9.15: 24.21-36.21: 0.61-0.92. When the reactant ratio is within this range, the material can fix the target pollutant in an aquatic environment where only the target pollutant exists. The efficiency can reach 70 mg / g or more.

[0057] Specifically, the mixed liquid further contains a solvent, and the solvent is selected from at least one of methanol, ethanol, acetic acid, and acetic acid; the volume of the solvent is 100 to 300 times that of 4-vinylpyridine.

[0058] Specifically, the specific conditions of reaction II include:

[0059] The process is carried out under stirring and inert atmosphere, wherein the inert atmosphere includes nitrogen, argon and the like;

[0060] React at 15-30°C for 50-60 min, raise the temperature to 50-60°C, and react for 10-12 h to avoid rapid decomposition of the initiator.

[0061] In an optional embodiment, the specific steps of preparing the biochar-based ion-imprinted polymer include:

[0062] Add 0.2-0.3g of sodium arsenite to the flask, then add 50-60ml of methanol, then add 0.2-0.3g of 4-vinylpyridine, seal the flask with a stopper or a sealing film, add a magnet, adjust the speed to 600-800rpm, stir for 20-30min, then add 1.8-2.5g of biochar, continue to stir for 20-30min, then add 0.8-1.3g of azobisisobutyronitrile, stir for 18-22min, and then introduce inert gas for 20-30min. Then, seal the container with a stopper and a sealing film, transfer to a constant temperature water bath, maintain a temperature of 57-62°C for 12-13h, and obtain the material.

[0063] The subsequent processing of materials is as follows:

[0064] The material is rinsed in a centrifuge tube with a hydrochloric acid solution having a concentration of 0.6 to 1.2 mol / l for 5 to 8 times, and then washed with pure water / deionized water until the material is neutral, and then transferred to an oven to dry at 60°C, and then ground with a mortar, screened with a 200 to 300 mesh steel sieve, and the finished product is sealed and stored.

[0065] The flask used in the preparation process can be a round-bottom flask or a three-necked flask.

[0066] The following are specific embodiments:

[0067] The biochar used in the embodiment of the present invention is prepared according to the method provided in the above biochar preparation embodiment, and the remaining raw materials are all commercially available products with a purity of premium grade or above.

[0068] Example 1

[0069] In a 100ml three-necked flask, add 0.13g of sodium arsenite, then add 0.45ml of high-grade pure 4-vinylpyridine (4-VP) as a ligand, add 100ml of methanol, use magnetic stirring (speed 800rpm) to dissolve sodium arsenite in methanol and seal it, react for 30min to form a complex. Then add 1.0 biochar and stir at 800rmp for 30min, then add 4.1ml ethylene glycol dimethacrylate and 0.1g azobisisobutyronitrile, and use magnetic stirring at 800rmp for 30min at room temperature. Nitrogen is introduced to drive out oxygen in the system for 20min, then the flask is sealed with a sealing film, and the reactants are reacted at 60℃ for 12h using a constant temperature method. The product generated by the reaction is washed with a water / methanol solution (volume ratio of 1:4). Then, the product was washed with 0.8 mol HCl solution to remove the template ions, and after washing 6 times, it was washed with ultrapure water until the washed liquid was neutral. The obtained product was dried in a vacuum environment at 60° C., then ground and passed through a 320-mesh sieve to obtain the finished product.

[0070] Example 2

[0071] In a 100ml three-necked flask, add 0.13g of sodium arsenite, then add 0.45ml of high-purity 4-vinylpyridine (4-VP) as a ligand, add 100ml of methanol, and use magnetic stirring (speed 800rpm) to dissolve sodium arsenite in methanol. Then add 1.0 biochar and stir at 800rmp for 30min, then add 4.1ml ethylene glycol dimethacrylate and 0.1g azobisisobutyronitrile, and use magnetic stirring at 800rmp for 30min at room temperature. Nitrogen is introduced to drive out oxygen in the system for 20min, then the flask is sealed with a sealing film, and the reactants are reacted at 60℃ for 12h using a constant temperature method. The product generated by the reaction is washed with a water / methanol solution (volume ratio of 1:4). Then, the template ions are removed by washing with a 0.8mol HCl solution. After washing 6 times, the product is washed with ultrapure water until the washed liquid is neutral. The obtained product was dried in a vacuum environment at 60° C., then ground and passed through a 320-mesh sieve to obtain a finished product.

[0072] Embodiments 3 to 5

[0073] The preparation method is basically the same as that of Example 1, and the differences are shown in Table 1.

[0074] Table 1 is the experimental parameters and experimental data of each embodiment

[0075]

[0076] The biochar-based arsenic ion imprinted polymers provided in each embodiment were characterized by electron microscopy scanning:

[0077] The morphology of the biochar and the biochar-based ion-imprinted polymer provided in Example 1 was observed using a scanning electron microscope (SEM). Figure 1 (a is biochar, b is biochar-based ion-imprinted polymer) It can be clearly observed that the ion-imprinted polymer is evenly distributed on the surface of the biochar in an ellipsoidal shape. Compared with biochar, the surface of the biochar-based ion-imprinted polymer is rougher and has more micropores. The biochar-based ion-imprinted polymer materials provided in other embodiments also have the same or similar morphology.

[0078] Taking the material provided in Example 1 as a typical representative, energy spectrum analysis was performed:

[0079] See also Figure 2 , the main components of biochar-based arsenic ion imprinted polymer are C and O, with the corresponding atomic percentage of 80:20.

[0080] The material provided in Example 1 was used as a typical representative to perform thermogravimetric analysis:

[0081] from Figure 3From the thermogravimetric curve of the biochar-based arsenic ion imprinted polymer, it can be seen that the material begins to decompose at 290°C and completes decomposition at 420°C, with a weight loss rate of 55.10%. It can be seen that the obtained material is relatively stable, not easily decomposed by heat, and can stably exist in a high temperature environment under natural conditions.

[0082] Taking the material provided in Example 1 as a typical representative, adsorption thermodynamic analysis was performed:

[0083] from Figure 4 By analyzing the results of adsorption thermodynamics (a is the Langmuir isotherm adsorption model, b is the Frueindlich isotherm adsorption model), it can be seen that the adsorption of arsenite ions by the material conforms to the Langmuir adsorption model and belongs to monolayer adsorption.

[0084] Application Example 1

[0085] The materials provided in each embodiment were used to test the adsorption performance of arsenite in water. The concentration of arsenite ions in the water was 100 mg / L, the material used for adsorption was 0.1 g material / L water, the adsorption conditions were 25°C and pH=7.0, and the adsorption amount of each embodiment is shown in Table 1.

[0086] Application Example 2

[0087] The biochar-based arsenic ion imprinted polymers provided in each embodiment were respectively tested for multi-ion system adsorption selectivity:

[0088] The test conditions include: the arsenite ion concentration in the water is 100 mg / L, the nitrate ion concentration is 100 mg / L, the chloride ion concentration is 100 mg / L, the material used for adsorption is 0.1 g material / L water, and the adsorption conditions are 25°C and pH=7.0.

[0089] Take the materials provided in Example 1 as an example, see Figure 5 , wherein IIP is the material provided in Example 1, NIP is the polymer finally prepared without adding sodium arsenite, and the remaining steps are the same as those in Example 1; Figure 5 The results show that the material has obvious selectivity for arsenite and can - , Cl - 、SO4 2- Accurately capture arsenite ions in common ion systems such as argon-containing compounds.

[0090] Application Example 3

[0091] The biochar-based arsenic ion imprinted polymers provided in each embodiment were subjected to a preliminary fixation test on a single arsenic pollution source blended soil in the laboratory:

[0092] Specific test conditions include: the total arsenic in the blending soil is 200 mg / kg, the amount of effective arsenic is 118 mg / kg, 0.6 g of the material that has passed through a 100-mesh sieve is weighed and added to 500 g of the blending soil, mixed, and then rinsed regularly. Soil samples are taken every week to determine the content of effective arsenic.

[0093] from Figure 6 The results show that the material has a good fixation effect on the effective arsenic in the soil of single arsenic pollutant, and the fixation efficiency can reach 45%. And the fixation achieved a stable effect in just 5 weeks, indicating that the material has a high short-term fixation efficiency for arsenic in the soil.

[0094] Application Example 4

[0095] The finished material provided in Example 1 was used to fix arsenic in high-concentration arsenic-containing soil near the site of an arsenic smelter. The effective arsenic content in the soil was about 100 mg / kg, and the amount of fixation material added was 1.2 g material / kg soil. After 5 weeks, the fixation reached stability, and the fixation effect reached about 38.40%.

[0096] from Figure 7 It can be seen that the biochar-based arsenic ion imprinted polymer has a good in-situ fixation effect on arsenic smelter tailings, and the fixation effect of trivalent arsenic and pentavalent arsenic can reach 35% to 40%. And the fixation reached stability in the fifth week of application, showing an excellent short-term fixation effect.

[0097] The above is only an embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various changes and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application should be included in the scope of the claims of the present application.

Claims

1. A method for preparing a biochar-based ion-imprinted polymer material, characterized in that: include: The mixed solution containing the template and 4-vinylpyridine is subjected to reaction I to obtain reaction system I, wherein the template is a metalloid compound or a heavy metal compound, and the specific conditions of reaction I include a reaction time of 25 to 35 minutes; Adding biochar, a cross-linking agent, and an initiator to the reaction system I to carry out reaction II, washing, and drying to obtain a biochar-based ion-imprinted polymer material, wherein the mass ratio of the template agent, 4-vinylpyridine, biochar, the cross-linking agent, and the initiator is 1: 2.72~4.08: 6.10~9.15: 24.21~36.21: 0.61~0.92; The specific conditions of reaction I include: Carry out under stirring conditions; The reaction temperature is 10~40℃; The template agent is sodium arsenite; The cross-linking agent is ethylene glycol dimethacrylate; The initiator is azobisisobutyronitrile; The mixed solution further comprises a solvent, and the solvent is selected from at least one of methanol, ethanol, acetic acid, and acetic acid; The amount of the solvent used is 100 to 300 times that of 4-vinylpyridine.

2. The preparation method according to claim 1, characterized in that: The specific conditions of reaction II include: Carry out under stirring and inert atmosphere; React at 15~30℃ for 50~60min, raise the temperature to 50~65℃, and react for 10~12h.

3. The biochar-based ion-imprinted polymer material prepared by the method of claim 1 or 2.

4. Application of the biochar-based ion-imprinted polymer material prepared by the method of claim 1 or 2 in the field of environmental remediation.

5. The use according to claim 4, characterized in that: Application in the fixation of arsenic contamination in soil.

Citation Information

Patent Citations

  • Preparation method of biochar with multiple heavy metal Cd adsorption sites

    CN112717891A